VoluntaRadio: un proyecto de responsabilidad social universitaria en el ámbito de la comunicación radial - Espinoza Espinoza, Pablo (2007)
This article is a reflection from a learning service experience addressed to radio communicators in different provinces of our country under the responsibility of the Department of Communication and students of thc School of Arts and Communication Sciences of the Pontificia Universidad Católica del Perú. This experience is within the framework of relations between university and Peruvian society. We emphasize thc pedagogical value of applied methodology, insertion strategics in local environments, radio troublesome matters as challenge for training and the intercultural value of this experience. VolunraRadio is a between academic training and services for villages and communities which seek to make radio a common mean in favor of local development.